Effect of Total Quality Management Implementation on Patient Satisfaction: A Six-Year Experience in a Public Hospital - ÇETİN, GÜVEN; ÇETİN, GÜVEN; Celik, Gurhan; Kaya, Fatih Oner; Gunes, Mehmet Emin; KESKİN, HALİT (My University, 2012)
Objectives: The purpose of this descriptive study was to investigate the effects of a total quality management system, which was implemented in a public hospital for six years, on patient satisfaction about health services.